Transgenic alfalfa plants co-expressing glutathione S-transferase (GST) and human CYP2E1 show enhanced resistance to mixed contaminates of heavy metals and organic pollutants - Zhang, Yuanyuan; Liu, Junhong (Journal of hazardous materials, 2011)
Transgenic alfalfa plants simultaneously expressing human CYP2E1 and glutathione S-transferase (GST) were generated from hypocotyl segments by the use of an Agrobacterium transformation system for the phytoremediation of the mixed contaminated soil with heavy metals and organic pollutants. The transgenic alfalfa plants were screened by a combination of kanamycin resistance, PCR, GST and CYP2E1 activity and Western blot analysis. The capabilities of mixed contaminants (heavy metals-organic compounds) resistance of pKHCG transgenic alfalfa plants became markedly increased compared with the transgenic alfalfa plants expressing single gene (GST or CYP2E1) and the non-transgenic control plants. The pKHCG alfalfa plants exhibited strong resistance towards the mixtures of cadmium (Cd) and trichloroethylene (TCE) that were metabolized by the introduced GST and CYP2E1 in combination. Our results show that the pKHCG transgenic alfalfa plants have good potential for phytoremediation because they have cross-tolerance towards the complex contaminants of heavy metals and organic pollutants. Therefore, these transgenic alfalfa plants co-expressing GST and human P450 CDNAs may have a great potential for phytoremediation of mixed environmental contaminants.